Method for forming plasma corrosion resistant coating for gas spray header

By forming a hydrogen bond passivation of silicon dioxide barrier layer on the inner wall of the spray head electrode pore, the problem of ceramic deposits falling into the pores is solved, and the effect of reducing particle contamination and improving chip product yield is achieved.

CN119588591APending Publication Date: 2025-03-11ADVANCED MICRO FAB EQUIP INC CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311160758.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In plasma equipment, ceramic coatings tend to fall into the pores of the spray head electrode during the deposition process, resulting in particle contamination, affecting the etching accuracy and the yield of the chip product.

Method used

A silica sol gel method is used to form a silicon dioxide layer on the anodized layer on the inner wall of the pore, and the surface of its hydrogen bond is passivated by heat treatment to form a barrier layer to resist the adhesion of ceramic deposits. Subsequently, the silica barrier layer is removed to avoid contamination.

Benefits of technology

It effectively isolates the possibility of ceramic deposits falling into the inner wall of the pores, reduces particle pollution, and improves the cleanliness of the etching equipment and the yield of chip products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588591A_ABST
    Figure CN119588591A_ABST
Patent Text Reader

Abstract

The invention discloses a method for forming a plasma corrosion resistant coating for a gas spray header, which comprises the following steps of: providing the gas spray header which is provided with a plurality of air holes penetrating through the front surface and the back surface of the gas spray header; the inner wall of the air hole is covered with an anodic oxide layer; forming a silicon dioxide layer on the anodic oxide layer on the inner wall of the air hole by adopting a silicon dioxide sol-gel method; performing heat treatment on the silicon dioxide layer to obtain a silicon dioxide barrier layer with a hydrogen bond passivation surface; forming a plasma corrosion resistant coating on the front surface of the gas spray head; and removing the silicon dioxide barrier layer. The silicon dioxide barrier layer resists adhesion of subsequent ceramic deposits to the inner walls of the pores and isolates the ceramic deposits from falling into the inner walls of the pores; when the silicon dioxide barrier layer is removed through wet etching, a small amount of ceramic deposits adhered to the surface of the silicon dioxide barrier layer are removed together, and loose ceramic deposits are further prevented from being formed on the inner walls of the pores.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor plasma etching equipment, and in particular to a method for forming a plasma corrosion resistant coating for a gas shower head. Background Art

[0002] In plasma equipment, ceramic coatings such as yttrium oxide are often used in the processing and preparation of corrosion-resistant parts. Among them, the ceramic coating of the shower head electrode is usually prepared by physical vapor deposition (PVD), chemical vapor deposition (CVD) or plasma spraying. However, during the deposition of the ceramic coating, the ceramic is not only deposited on the surface of the shower head electrode, but also deposited in the pores. Due to the contact angle, the bonding force between the ceramic deposited in the pore and the pore wall is relatively weak, and ceramic particle contaminants are easily dropped after the equipment has been running for a period of time.

[0003] As the integrated circuit manufacturing technology node breaks through to the 3nm process, the cleanliness requirements for the plasma etching equipment reaction chamber are becoming higher and higher. Particle contaminants appearing in the reaction chamber will greatly affect the etching accuracy or cause critical defects, thereby affecting the yield of chip products. Summary of the invention

[0004] The object of the present invention is to provide a method for forming a plasma corrosion resistant coating for a gas shower head, so as to prevent ceramic deposits from falling into the pores of the shower head electrode and reduce particle contamination.

[0005] In order to achieve the above object, the present invention provides a method for forming a plasma corrosion resistant coating for a gas shower head, comprising the following steps:

[0006] A gas shower head is provided, which is provided with a plurality of air holes penetrating the front and back of the gas shower head; the inner walls of the air holes are covered with an anodized layer;

[0007] forming a silicon dioxide layer on the anodic oxide layer on the inner wall of the pore by using a silicon dioxide sol-gel method;

[0008] thermally treating the silicon dioxide layer to obtain a silicon dioxide barrier layer having a hydrogen bond passivated surface;

[0009] forming a plasma corrosion resistant coating on the front surface of the gas shower head;

[0010] The silicon dioxide barrier layer is removed.

[0011] Optionally, the back side of the gas shower head is covered with an anodized layer, and before forming the silicon dioxide layer, the method further comprises: covering the front and back sides of the gas shower head with a first protective film; after forming the silicon dioxide layer, removing the first protective film and performing the subsequent heat treatment step.

[0012] Optionally, after the step of forming the plasma corrosion resistant coating, a second protective adhesive film is covered on the front side of the plasma corrosion resistant coating to protect the plasma corrosion resistant coating; after removing the silicon dioxide barrier layer, the second protective adhesive film is removed.

[0013] Optionally, the heat treatment is performed at a temperature of 200° C. to 500° C. and for a time of 0.5 hour to 3 hours.

[0014] Optionally, before the heat treatment, the silicon dioxide layer is further baked and cured, and the baking and curing temperature is 80° C. to 120° C. and the time is 1 hour to 2 hours.

[0015] Optionally, the silicon dioxide layer is formed by an immersion pulling method.

[0016] Optionally, the rate of the immersion pulling is 1 cm / min to 20 cm / min.

[0017] Optionally, the silica sol-gel system used in the silica sol-gel method has a viscosity of 1 mPa·s to 6 mPa·s.

[0018] Optionally, the silicon dioxide layer has a thickness of 0.1 μm to 10 μm.

[0019] Optionally, wet etching is used to remove the silicon dioxide barrier layer.

[0020] Optionally, the temperature of the wet etching is 20° C. to 30° C., and the etching time is 1 min to 100 min.

[0021] Optionally, the material of the plasma corrosion resistant coating includes at least one of yttrium oxide, yttrium fluoride or yttrium oxyfluoride.

[0022] Optionally, a reinforcement barrier layer is further formed between the heat treatment step and the step of forming the plasma corrosion resistant coating.

[0023] Optionally, the formation of the enhanced barrier layer comprises the following steps:

[0024] Using a vapor deposition process, forming an enhanced barrier layer on the surface of the silicon dioxide barrier layer;

[0025] The gas phase deposits on the front surface of the gas shower head are removed by sandblasting.

[0026] Optionally, the deposition temperature of the deposition process is no greater than 600°C.

[0027] Optionally, the deposition process includes plasma enhanced chemical vapor deposition or atomic layer deposition.

[0028] Optionally, the material of the enhanced barrier layer includes silicon dioxide, silicon carbide or silicon nitride.

[0029] Optionally, the thickness of the enhanced barrier layer is 1 nm to 100 nm.

[0030] Optionally, the first protective adhesive film and the second protective adhesive film have openings corresponding to the size and number of the pores.

[0031] Optionally, the materials of the first protective adhesive film and the second protective adhesive film include a photoresist film or an acid- and alkali-resistant film.

[0032] Compared with the prior art, the beneficial effects of the technical solution of the present invention include at least:

[0033] (1) The method for forming a plasma corrosion resistant coating for a gas shower head provided by the present invention, before depositing a plasma corrosion resistant coating such as ceramic, uses a sol-gel method and an immersion-pulling method to form a silicon dioxide layer on the surface of the inner wall of the gas shower head electrode. The silicon dioxide layer has a small number of surface hydrogen bonds after heat treatment. In the subsequent deposition process of the plasma corrosion resistant coating, it can resist the adhesion of ceramic deposits and isolate the ceramic deposits from falling into the inner wall of the pores to avoid particle contamination. When the silicon dioxide barrier layer is subsequently removed by wet etching, the present invention also removes a small amount of ceramic deposits adhering to the surface of the silicon dioxide barrier layer, further avoiding the formation of loose ceramic deposits in the pores. In addition, the reason why the present invention uses wet etching to remove the silicon dioxide barrier layer instead of additionally depositing a plasma resistant coating such as yttrium oxide on the silicon dioxide barrier layer is to avoid new pollution caused by the reaction of silicon with fluorine in the process gas, which helps to improve the yield of chip products.

[0034] (2) The use of a double barrier layer can better isolate the possibility of ceramic deposits falling into the inner wall of the pore. Specifically, a denser enhanced barrier layer with fewer surface hydrogen bonds is formed on the surface of the silicon dioxide layer through a PECVD or ALD process. The silicon dioxide layer and the enhanced barrier layer constitute a double barrier layer, which further enhances the anti-adhesion effect of the inner wall of the pore on ceramic deposits.

[0035] (3) During the etching process of the silicon dioxide layer of the present invention, the plasma corrosion resistant coating on the surface of the gas shower head is protected by using a protective film, thereby avoiding adverse effects on the corrosion resistance of the gas shower head.

[0036] (4) The preparation process of the present invention is simple, the effect is good, the service life and performance of semiconductor components are extended, the cost of equipment use is saved, and it is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The present invention is a flowchart of a method for forming a plasma corrosion resistant coating for a gas shower head according to an embodiment of the present invention.

[0038] Figures 2 to 3 It is a schematic diagram of the structure of a gas shower head during the formation process of one embodiment of the present invention and a partially enlarged schematic diagram of the structure of the inner wall of the pore.

[0039] Figure 4 The flowchart is a method for forming a plasma corrosion resistant coating for a gas shower head according to another embodiment of the present invention.

[0040] Figure 5 FIG. 1 is a schematic diagram of the structure of a gas shower head during the formation process of another embodiment of the present invention.

[0041] Figure 6 FIG. 4 is a flow chart of a method for forming a plasma corrosion resistant coating for a gas shower head according to another embodiment.

[0042] Figure 7 It is a partially enlarged schematic diagram of the inner wall structure of the pore during the formation process of another embodiment of the present invention.

[0043] Figure 8 SEM images of the pore inner wall structures of Example 1 and Comparative Example 1.

[0044] Figure ID:

[0045] Gas shower head 1, air hole 11, anodized layer 2, silicon dioxide layer 3', silicon dioxide barrier layer 3, plasma corrosion resistant coating 4, and enhanced barrier layer 5. DETAILED DESCRIPTION

[0046] In order to solve the above technical problems, an embodiment of the present invention provides a method for forming a plasma corrosion resistant coating for a gas shower head.

[0047] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0049] It should also be noted that when an element is referred to as being "fixed on" or "disposed on" another element, it may be directly on the other element or there may be an intermediate element at the same time. When an element is referred to as being "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.

[0050] As described in the background technology, ceramic coatings such as yttrium oxide are often used in the processing and preparation of semiconductor corrosion-resistant components. However, in the preparation process of ceramic coatings such as yttrium oxide, it is difficult to avoid ceramic deposits from falling into the pores of the shower head electrode. After research, it was found that after the shower head electrode prepared by the prior art runs for a large number of RF hours, ceramic deposits on the inner wall of the shower head electrode pores will fall off, such as yttrium oxide ceramic particles and yttrium fluoride ceramic particles. If these particles fall on the surface of the wafer, the yield of the integrated circuit product will decrease. Therefore, some researchers have proposed to use polymer or metal plugs to plug the pores before the preparation process of ceramic coating to prevent ceramic deposits from falling into the pores. However, polymers are usually difficult to withstand the high temperature of about 250℃ to 900℃ during the preparation process of ceramic coating. Under high temperature conditions, polymers will quickly carbonize or vaporize, forming organic pollutants that pollute parts and cavities; and metals are usually prone to interfacial diffusion and migration of metal atoms at high temperatures, which can easily remain on the shower head electrode and cause metal contamination during the etching process. In addition, metal plugs usually require manual operation, and thousands of holes need to be plugged manually, which is very time-consuming and labor-intensive. The "RF hours" in this article are the time used to generate plasma using radio frequency power, measured in hours.

[0051] In summary, the existing method of preparing ceramic coating on the surface of the shower head electrode is difficult to prevent ceramic deposits from falling into the pores of the shower head electrode. Even if the pores of the shower head electrode are blocked by polymer or metal plugs, new pollution will be generated, causing particle contamination of the shower head electrode during subsequent use, resulting in a decrease in the yield of chip products and failure to meet application requirements.

[0052] To solve the above technical problems, Figure 1 To Attachment Figure 3 As shown, an embodiment of the present invention provides a method for forming a plasma corrosion resistant coating for a gas shower head, comprising:

[0053] Step 101 , providing a gas shower head 1 .

[0054] The gas shower head 1 is provided with a plurality of gas holes 11 penetrating the front and back of the gas shower head 1 , and the process gas is uniformly supplied to the reaction chamber through the gas holes 11 ;

[0055] The inner wall of the pore 11 is covered with an anodized layer 2, so that the inner wall of the pore 11 has the function of resisting corrosive gas. The anodized layer 2 is anodized aluminum, and its preparation process belongs to the conventional technology in the field, which will not be described here.

[0056] After this step, the gas shower head 1 and the coating structure on its surface are as follows: Figure 2 As shown in (a).

[0057] Step 102 : forming a silicon dioxide layer 3 ′ on the anodized layer 2 on the inner wall of the pore 11 by using a silicon dioxide sol-gel method.

[0058] The present invention utilizes the hydrogen bonding force between silicon dioxide and the surface of the anodized layer 2 on the inner wall of the pore 11, and prepares a regular and orderly silicon dioxide layer 3' with controllable thickness as a barrier layer on the surface of the anodized layer 2 by an interface self-assembly method, and the silicon dioxide layer 3' isolates the possibility of ceramics such as yttrium oxide being deposited on the surface of the anodized layer 2 on the inner wall of the pore 11. In addition, the melting point of silicon dioxide is 1723°C, which can withstand the temperature requirements (about 250°C to 900°C) during the ceramic coating preparation process, and does not generate new pollution or other side effects.

[0059] As an example, the preparation method of the silica sol-gel system adopted in this embodiment is: prepare a mixed solution containing 20v%~40v% tetraethyl silicate (TEOS), 27v%~65.8v% anhydrous ethanol (EtOH), 10v%~20v% ultrapure water and 4v%~12v% glycerol; under 30℃~60℃ conditions, add an acid catalyst to the mixed solution, stir the hydrolysis reaction for 3 hours to 6 hours, and after the reaction is completed, age at room temperature for 3 days to 10 days to obtain the silica sol-gel system. Among them, compared with the use of base catalysis to prepare the silica sol-gel system, the use of acid catalysis to prepare the silica sol-gel system has the advantage of making the subsequent silica layer 3' have stronger adhesion. The reason is that: after acid-catalyzed hydrolysis, TEOS can form a linear silica gel, which has strong adhesion, low porosity, and extremely strong friction resistance; while after base-catalyzed hydrolysis, TEOS mainly generates silica nanoparticles, which are randomly stacked together, and the particles are mainly connected by non-chemical bonds such as van der Waals forces. Therefore, the silica layer 3' has poor adhesion and is easy to fall off, thereby losing its blocking effect and forming particulate pollutants.

[0060] In some embodiments, the silicon dioxide layer 3' is formed by an immersion pulling method. The present invention finds that the viscosity of the silicon dioxide sol-gel system and the rate of immersion pulling are key factors affecting the thickness and surface flatness of the silicon dioxide layer 3'. Specifically:

[0061] As an example, the viscosity of the silica sol-gel system is 1mPa·s to 6mPa·s. When the viscosity is between 1mPa·s and 6mPa·s, the greater the viscosity, the thicker the formed silica barrier layer, and the smooth and flawless the surface, which plays an effective barrier role and is conducive to the subsequent complete and residue-free removal of the silica layer 3' through the etching process; and when the viscosity is not in the range of 1mPa·s to 6mPa·s, it is easy to form a silica layer 3' with insufficient thickness or uneven surface and uneven thickness. Among them, when the viscosity is less than 1mPa·s, the formed silica layer 3' is thin, and the surface is uneven and defective; when the viscosity is greater than 6mPa·s, due to the excessive viscosity, the formed silica layer 3' is prone to orange peel phenomenon, and the uniformity of the silica layer 3' deteriorates, and the phenomenon of thick top and thin bottom will appear. It can be understood that when the silicon dioxide layer 3' is not thick enough, it is difficult to play an effective blocking role; when the surface of the silicon dioxide layer 3' is uneven or the thickness is uneven, it is difficult to completely remove the silicon dioxide layer 3' when it is subsequently removed by an etching process, and it is easy to leave residues. The residual silicon dioxide will react with the fluorine in the process gas to produce new particle pollution.

[0062] In addition, as an example, the rate of the immersion pulling is 1 cm / min to 20 cm / min. It can be understood that the faster the immersion pulling rate is, the thinner the thickness of the silicon dioxide layer 3' is, and it is difficult to play an effective barrier role; the slower the immersion pulling rate is, the thicker the thickness of the silicon dioxide layer 3' is, which causes unnecessary waste of raw materials and reduces production efficiency.

[0063] After this step, the gas shower head 1 and the coating structure on its surface are as follows: Figure 2 As shown in (b), Figure 3 It is an enlarged schematic diagram of the coating structure on the surface of the pore 11.

[0064] Step 103 , heat-treating the silicon dioxide layer 3 ′ to obtain a silicon dioxide barrier layer 3 having a hydrogen bond passivated surface.

[0065] Because the surface of silicon dioxide contains a large number of Si-OH groups, in the subsequent preparation process of the plasma corrosion resistant coating 4, when the gaseous substances of ceramics such as yttrium oxide or the newly formed yttrium oxide nanoparticles pass through the pores 11, the ceramics such as yttrium oxide are easily adhered to the silicon dioxide layer 3' through the force of hydrogen bonds, which greatly increases the probability of ceramic deposition in the pores 11. In order to solve this problem, step 103 of this embodiment proposes to heat treat the silicon dioxide layer 3', at least to volatilize the H2O on the surface of the silicon dioxide layer 3' (the reaction mechanism is: [SiO2] m ·nSiO3 2- 2nH + →[SiO2] m+x ·(nx)SiO3 2- ·2(nx)H + +xH2O), thereby greatly reducing the hydrogen bond content on the surface of the silicon dioxide layer 3', and obtaining a silicon dioxide barrier layer 3 with a hydrogen bond passivated surface. In addition, the heat treatment will also make the silicon dioxide layer smoother and denser.

[0066] It should be emphasized that the passivated hydrogen bonds refer to the hydrogen bonds exposed on the surface of the silicon dioxide layer 3', not the hydrogen bonds bonded to the anodized layer 2 on the inner wall of the pore 11. Therefore, the heat treatment temperature should not be too high. As an example, the heat treatment temperature is 200℃~500℃, and the time is 0.5 hour~3 hours. Within this temperature range, good passivation hydrogen bonding is guaranteed, and no damage is caused to the substrate such as aluminum alloy (the melting point of aluminum alloy is about 580℃-650℃).

[0067] In some embodiments, before the heat treatment, the silicon dioxide layer 3' is further baked and cured, and the baking and curing temperature is 80°C to 120°C, and the time is 1 hour to 2 hours. The purpose of baking is mainly to remove water and ethanol solvent in the silicon dioxide sol-gel, further enhance the thermal cross-linking of linear silicon dioxide, and make the silicon dioxide layer 3' denser.

[0068] After this step, the gas shower head 1 and the coating structure on its surface have no significant changes compared to the previous step. The difference is that after the surface of the silicon dioxide layer 3 ′ is heat treated, the surface hydrogen bond content is reduced to form the silicon dioxide barrier layer 3 .

[0069] Step 104, forming a plasma corrosion resistant coating 4 on the front surface of the gas shower head 1;

[0070] The material of the plasma corrosion resistant coating 4 includes at least one of yttrium oxide, yttrium fluoride or yttrium oxyfluoride. The plasma corrosion resistant coating 4 is used to improve the plasma corrosion resistance of the gas shower head 1 to prevent it from being corroded by plasma during long-term use. Among them, preparing the plasma corrosion resistant coating 4 on the surface of the gas shower head 1 belongs to the conventional technology in the field and will not be described here.

[0071] After this step, the gas shower head 1 and the coating structure on its surface are as follows: Figure 2 As shown in (c).

[0072] Step 105 , removing the silicon dioxide barrier layer 3 .

[0073] As mentioned above, silicon dioxide will react with fluorine in the process gas to cause new particle pollution. Therefore, after the preparation of the plasma corrosion resistant coating 4 is completed, the silicon dioxide barrier layer 3 needs to be removed. In addition, this step also has the following benefits: when preparing the plasma corrosion resistant coating 4, even if a small amount of ceramics such as yttrium oxide, yttrium fluoride, and yttrium oxyfluoride are deposited in the pores 11, they will be completely removed in the subsequent removal of the silicon dioxide barrier layer 3, preventing the ceramic deposits from falling into the pores 11 of the gas shower head 1, thereby avoiding particle pollution.

[0074] In some embodiments, wet etching is used to remove the silicon dioxide barrier layer 3. The temperature of the wet etching is 20°C to 30°C, and the etching time is 1 min to 100 min.

[0075] After this step, the gas shower head 1 and the coating structure on its surface are as follows: Figure 2 As shown in (d), a gas shower head 1 having the plasma corrosion resistant coating 4 is finally obtained, and the plasma corrosion resistant coating 4 is prevented from falling into the inner wall of the pore 11 during the deposition process, thereby reducing particle contamination during subsequent use.

[0076] like Figure 4 and Figure 5 As shown, an embodiment of the present invention provides another method for forming a plasma corrosion resistant coating for a gas shower head, which is an improvement on the method of the aforementioned embodiment, and provides a method for preventing ceramic deposits from falling into the inner wall of the pore 11 without affecting the anodized layer 2 and the plasma corrosion resistant coating 4 when the back of the gas shower head 1 is also covered with the anodized layer 2. Specifically, it includes:

[0077] Step 201 , providing a gas shower head 1 .

[0078] The gas shower head 1 is provided with a plurality of air holes 11 penetrating the front and back of the gas shower head 1 ; the back of the gas shower head 1 and the inner walls of the air holes 11 are covered with an anodized layer 2 . It should be noted that the front of the gas shower head 1 refers to the surface exposed to plasma.

[0079] After this step, the gas shower head 1 and the coating structure on its surface are as follows: Figure 5 As shown in (a).

[0080] Step 202 : Covering the front and back sides of the gas shower head 1 with a first protective film.

[0081] The first protective film is used to prevent silicon dioxide from being deposited on the anodized layer 2 on the front and back sides of the gas shower head 1 when the silicon dioxide layer 3' in the subsequent pores 11 is prepared, thereby reducing the corrosion resistance of the front and back sides of the gas shower head 1.

[0082] Step 203 : forming a silicon dioxide layer 3 ′ on the anodized layer 2 on the inner wall of the pore 11 by using a silicon dioxide sol-gel method.

[0083] After this step, the gas shower head 1 and the coating structure on its surface are as follows: Figure 5 As shown in (b).

[0084] Step 204: removing the first protective film.

[0085] The purpose of this step is to prevent the first protective adhesive film from being carbonized during subsequent heat treatment to generate new pollution.

[0086] Step 205 , heat-treating the silicon dioxide layer 3 ′ to obtain a silicon dioxide barrier layer 3 having a hydrogen bond passivated surface.

[0087] After this step, the gas shower head 1 and the coating structure on its surface have no significant changes compared to step 203 , except that the surface hydrogen bond content of the silicon dioxide layer 3 ′ is reduced after heat treatment, forming the silicon dioxide barrier layer 3 .

[0088] Step 206 : forming a plasma corrosion resistant coating 4 on the front surface of the gas shower head 1 .

[0089] After this step, the gas shower head 1 and the coating structure on its surface are as follows: Figure 5 As shown in (c).

[0090] Step 207 , covering the front surface of the plasma corrosion resistant coating 4 with a second protective adhesive film.

[0091] The second protective adhesive film is used to protect the plasma corrosion resistant coating 4 to prevent the subsequent process of removing the silicon dioxide barrier layer 3 from etching the plasma corrosion resistant coating 4 and affecting the corrosion resistance of the plasma corrosion resistant coating 4.

[0092] Step 208 , removing the silicon dioxide barrier layer 3 .

[0093] After this step, the gas shower head 1 and the coating structure on its surface are as follows: Figure 5 As shown in (d), a gas shower head 1 having the plasma corrosion resistant coating 4 is finally obtained, and the plasma corrosion resistant coating 4 is prevented from falling into the inner wall of the pore 11 during the deposition process, thereby reducing particle contamination during subsequent use. Meanwhile, during the formation process, the corrosion resistance of the anodized layer 2 and the plasma corrosion resistant coating 4 is protected by using the first protective adhesive film and the second protective adhesive film.

[0094] Step 209: removing the second protective film.

[0095] This step is to prevent the second protective film from being carbonized under high temperature conditions in subsequent process steps, thereby preventing new pollution.

[0096] like Figure 6 and Figure 7 As shown, the present invention provides another method for forming a plasma corrosion resistant coating for a gas shower head to further improve the isolation and barrier effect of ceramic deposits falling into the inner wall of the pore 11. This method improves the anti-adhesion effect of the barrier layer on the ceramic deposits through a double barrier layer combination, further reducing the possibility of ceramic deposits falling into the inner wall of the pore 11. The specific steps of the method of this embodiment are as follows Figure 6 As shown, compared with the aforementioned forming method, the forming method of this embodiment is different in that, between the heat treatment step and the step of forming the plasma corrosion resistant coating 4, a step is further included: forming an enhanced barrier layer 5, and the formation of the enhanced barrier layer 5 includes the following steps:

[0097] Step 306 , forming a reinforcement barrier layer 5 on the surface of the silicon dioxide layer 3 by using a vapor deposition process.

[0098] In some embodiments, considering that the melting point of aluminum alloy is about 580-650° C., the deposition temperature of the deposition process is not greater than 600° C. As an example, the deposition process includes plasma enhanced chemical vapor deposition (PECVD) or atomic layer deposition (ALD). Compared with the silicon dioxide layer prepared by the silicon dioxide sol-gel method and obtained by heat treatment, the enhanced barrier layer 5 prepared by these deposition processes has a higher density and fewer surface hydrogen bonds and active sites, thereby having a better anti-adhesion effect on ceramic deposits, further reducing the probability of ceramic deposits forming on the inner wall of the shower head electrode pores 11.

[0099] The material of the enhanced barrier layer 5 meets two requirements: (1) the deposition temperature is lower than 600° C.; (2) the number of surface hydrogen bonds and active sites is small. As an example, the material of the enhanced barrier layer 5 includes silicon dioxide or silicon nitride.

[0100] After this step, the coating structure on the surface of the pore 11 of the gas shower head 1 is as follows: Figure 7 As shown, the silicon dioxide layer 3 and the enhanced barrier layer 5 are sequentially formed on the anodized layer 2 on the inner wall of the pore 11 of the gas shower head 1. In some embodiments, the thickness of the silicon dioxide layer 3 is 0.1 μm to 10 μm, and the thickness of the enhanced barrier layer 5 is 1 nm to 100 nm. It can be understood that although the coating formed by PECVD or ALD has high density and few surface active sites and hydrogen bonds, these deposition processes have slow deposition rates and high costs, and are therefore not suitable for forming thicker barrier layer structures.

[0101] Step 307 : using a sandblasting process to remove the gas phase deposits on the front surface of the gas shower head 1 .

[0102] It should be noted that in this embodiment, when the enhanced barrier layer 5 is formed in step 306, it is difficult to avoid the formation of vapor deposits on the front surface of the gas shower head 1. Therefore, in this step, a physical method such as a sandblasting process is used to remove the vapor deposits on the front surface of the gas shower head 1. In addition, vapor deposits are usually not deposited on the back surface of the gas shower head 1. Even if there is a small amount of vapor deposits, they will be removed together when the silicon dioxide barrier layer 3 is removed by subsequent wet etching.

[0103] Example 1

[0104] This embodiment provides a method for forming a plasma corrosion resistant coating for a gas shower head, which specifically includes:

[0105] Step 301 , providing a gas shower head 1 . The gas shower head 1 is provided with a plurality of air holes 11 penetrating the front and back of the gas shower head 1 ; the back of the gas shower head 1 and the inner walls of the air holes 11 are covered with an anodized layer 2 .

[0106] Step 302: In a Class 100 clean room, use a 70 μm thick Nitto Denko SPV-224S acid- and alkali-resistant film to protect the anodized aluminum layer 2 on the back and front of the preliminarily processed and cleaned shower head electrode (before ceramic coating is prepared).

[0107] Step 303 : forming a silicon dioxide layer 3 ′ on the anodized layer 2 on the inner wall of the pore 11 by using a silicon dioxide sol-gel method and an immersion-coating method.

[0108] The preparation method of the silica sol-gel system is as follows: prepare a mixed solution containing TEOS, EtOH, ultrapure water and glycerol, wherein the content of TEOS in the mixed solution is 20-40v%, the content of EtOH is 27-65.8v%, the content of ultrapure water is 10-20v%, and the content of glycerol is 4-12v%. Then, under the condition of heating in a water bath at 30-60 degrees Celsius, 0.2-1v% concentrated hydrochloric acid (37%) is added dropwise, and the hydrolysis reaction is stirred for 3-6 hours. After the stirring is completed, the sol-gel system is aged for 3-10 days at room temperature (25°C), and the sol-gel system is used when the viscosity reaches 1mPa·s to 6mPa·s.

[0109] Step 304, removing the acid- and alkali-resistant adhesive film.

[0110] Step 305, using baking and annealing process to make the silicon dioxide layer 3' more dense and firm, the baking time is controlled at 1 to 2 hours, and the baking temperature is 80°C to 120°C; then the silicon dioxide layer 3' is heat treated (i.e., annealing process) to obtain a silicon dioxide barrier layer 3 with a hydrogen bond passivated surface, the heat treatment temperature is 200°C to 500°C, and the time is 0.5 hour to 3 hours.

[0111] Step 306: Using PECVD process, a reinforcement barrier layer 5 is formed on the surface of the silicon dioxide layer 3. The temperature of the PECVD process is controlled below 500°C.

[0112] Step 307 : using a sandblasting process to remove the gas phase deposits on the front surface of the gas shower head 1 .

[0113] Step 308 : forming a plasma corrosion resistant coating 4 on the front surface of the gas shower head 1 .

[0114] Step 309 : In a Class 100 clean room, use a 70 μm thick Nitto Denko SPV-224S acid- and alkali-resistant adhesive film to protect the front surface of the plasma corrosion-resistant coating 4 .

[0115] Step 310: remove the silicon dioxide barrier layer 3 and the enhanced barrier layer 5 by wet etching.

[0116] The etching solution is an acidic hydrofluoric acid system etching solution from Hubei Xingfu Electronic Materials Co., Ltd. The temperature of wet etching is 20°C to 30°C, and the etching time is 1min to 100min. Since the etching solution contains corrosion inhibitors such as catechol and its derivatives, aminopropionamide and its derivatives, naphthalenesulfonic acid and its derivatives, it will not corrode the anodized aluminum layer 2 in the hole and on the back.

[0117] Step 311, remove the acid-alkali resistant adhesive film covering the front side of the plasma corrosion resistant coating 4, use ultrapure water (UPW) to clean it under ultrasonic conditions in a clean room; remove a small amount of contaminants remaining on the shower head electrode during the process, and then use high-purity nitrogen to blow dry the cleaned shower head electrode, and finally use an oven to heat and dry it to remove the residual moisture on the gas shower head 1.

[0118] Comparative Example

[0119] The difference from Example 1 is that the silicon dioxide layer 3 and the enhanced barrier layer 5 are not formed.

[0120] The pores of the shower head electrodes prepared in Example 1 and the comparative example were cut open and observed using a scanning electron microscope (SEM). The results are as follows: Figure 8 As shown in Figure 2, the inner wall of the pores without the barrier layer is filled with more ceramic deposits such as yttrium oxide, especially in the upper part of the pores ( Figure 8 a), while the inner wall of the pores of the shower head electrode prepared by the scheme of the present invention has no ceramic deposits such as yttrium oxide ( Figure 8 (b)

[0121] Furthermore, the treated gas shower head 1 was installed on a plasma etching device for online testing. The single service life of the new shower head electrode increased from 800RFh when the barrier layer preparation process was not used to 1500RFh when the barrier layer preparation process was used, indicating the effectiveness of the barrier layer solution of the present invention.

[0122] To summarize, before preparing the plasma-resistant coating of the gas shower head, the present invention first forms a silicon dioxide barrier layer on the inner wall of the gas shower head pore, and the barrier layer resists the subsequent adhesion of ceramic deposits to the inner wall of the pore, thereby isolating the ceramic deposits from falling into the inner wall of the pore; when the silicon dioxide barrier layer is subsequently removed by wet etching, a small amount of ceramic deposits adhering to the surface of the silicon dioxide barrier layer are also removed, thereby further avoiding the formation of loose ceramic deposits in the pores, avoiding ceramic deposit particle contamination during the subsequent use of the gas shower head, and improving the yield of chip products.

[0123] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for forming a plasma corrosion resistant coating for a gas shower head, characterized in that: The following steps are involved: A gas shower head is provided, which is provided with a plurality of air holes penetrating the front and back of the gas shower head; the inner walls of the air holes are covered with an anodized layer; forming a silicon dioxide layer on the anodic oxide layer on the inner wall of the pore by using a silicon dioxide sol-gel method; thermally treating the silicon dioxide layer to obtain a silicon dioxide barrier layer having a hydrogen bond passivated surface; forming a plasma corrosion resistant coating on the front surface of the gas shower head; The silicon dioxide barrier layer is removed.

2. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 1, wherein: The back side of the gas shower head is covered with an anodic oxide layer. Before forming the silicon dioxide layer, the method further comprises: covering the front side and the back side of the gas shower head with a first protective film; After the silicon dioxide layer is formed, the first protective film is removed and then the subsequent heat treatment step is performed.

3. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 2, wherein: After the step of forming the plasma corrosion resistant coating, covering the front surface of the plasma corrosion resistant coating with a second protective adhesive film to protect the plasma corrosion resistant coating; After removing the silicon dioxide barrier layer, the second protective film is removed.

4. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 1, wherein: The heat treatment temperature is 200° C. to 500° C., and the time is 0.5 hour to 3 hours.

5. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 4, wherein: Before the heat treatment, the silicon dioxide layer is baked and cured. The baking and curing temperature is 80° C. to 120° C. and the time is 1 hour to 2 hours.

6. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 1, wherein: The silicon dioxide layer is formed by a dip-pull method.

7. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 6, wherein: The rate of the immersion pulling is 1 cm / min to 20 cm / min.

8. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 1, wherein: The viscosity of the silica sol-gel system used in the silica sol-gel method is 1 mPa·s to 6 mPa·s.

9. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 1, wherein: The thickness of the silicon dioxide layer is 0.1 μm to 10 μm.

10. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 1, wherein: The silicon dioxide barrier layer is removed by wet etching.

11. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 10, characterized in that: The temperature of the wet etching is 20° C. to 30° C., and the etching time is 1 min to 100 min.

12. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 1, wherein: The material of the plasma corrosion resistant coating includes at least one of yttrium oxide, yttrium fluoride or yttrium oxyfluoride.

13. The method for forming a plasma corrosion resistant coating for a gas shower head according to any one of claims 1 to 12, characterized in that: Between the heat treatment step and the step of forming the plasma corrosion resistant coating, the method further comprises the step of forming a reinforcement barrier layer.

14. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 13, wherein: The formation of the enhanced barrier layer comprises the following steps: Using a vapor deposition process, forming an enhanced barrier layer on the surface of the silicon dioxide barrier layer; The gas phase deposits on the front surface of the gas shower head are removed by sandblasting.

15. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 14, wherein: The deposition temperature of the deposition process is no greater than 600°C.

16. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 15, characterized in that: The deposition process includes plasma enhanced chemical vapor deposition or atomic layer deposition.

17. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 13, wherein: The material of the enhanced barrier layer includes silicon dioxide, silicon carbide or silicon nitride.

18. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 13, wherein: The thickness of the enhanced barrier layer is 1 nm to 100 nm.

19. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 13, wherein: The first protective adhesive film and the second protective adhesive film have openings corresponding to the size and number of the pores.

20. The method for forming a plasma corrosion resistant coating for a gas shower head according to claim 13, wherein: The materials of the first protective film and the second protective film include a photoresist film or an acid- and alkali-resistant film.

Citation Information

Cited By

  • Heat-insulating corrosion-resistant coating for semiconductor spray header and preparation method of heat-insulating corrosion-resistant coating

    CN121428452A